Evaluation of the impact of S-adenosylhomocysteine metabolic pools on cytosine methylation of the tobacco genome - Fojtová, M; Kovarík, A; Votruba, I; Holý, A (European journal of biochemistry, 1998)
We explored the possibility that the cytosine DNA methylation might be regulated by S-adenosyl-L-methionine (AdoMet) and S-adenosyl-L-homocysteine (AdoHcy) pools in plant cells. In order to change the AdoHcy/AdoMet ratio (methylation index), (S)-9-(2,3-dihydroxypropyl)adenine was employed, a selective reversible inhibitor of cellular S-adenosyl-L-homocysteine hydrolase. Micromolar concentrations of the inhibitor increased dramatically (more than 1000-fold) intracellular AdoHcy levels (and concominantly the AdoHcy/AdoMet ratio) in tobacco TBY-2 cells. No toxic effect of the drug was observed and the cells displayed only marginal inhibition of growth at high AdoHcy levels. At near equal intracellular concentrations of AdoHcy and AdoMet, a significant reduction of cytosine methylation in transcribed (5SrDNA) and non-transcribed (HRS60, NTRS) sequences was observed. Interestingly, the CpCpG and CpApG trinucleotide targets appeared to be most sensitive to changes in the methylation index. Methylation of cytosine residues at CpG sites was not affected even at AdoHcy/AdoMet ratio of > 10. These results support the possible regulation of DNA methylation via AdoHcy/AdoMet metabolic pathways in plant cells.
Keywords: DNA Methylation; Cell Line; Genome, Plant; genom rostlinný; Adenine; metylace DNA; RNA, Ribosomal, 5S; S-adenosylmethionin; adenin; ribozomální DNA; S-Adenosylhomocysteine; S-adenosylhomocystein; Plants, Toxic; DNA rostlinná; DNA, Plant; jedovaté rostliny; RNA ribozomální 5S; S-Adenosylmethionine; Nicotiana; buněčné linie; DNA, Ribosomal; tabák